Synthesis of Two Stereoisomers of Potentially Bioactive 13,19,20-Trihydroxy Derivative of Docosahexaenoic Acid - Ogawa, Narihito; Sone, Shinsaku; Hong, Song; Lu, Yan; Kobayashi, Yuichi (Synlett, 2020)
The C16–C22 fragment with the acetylene terminus was constructed through the asymmetric dihydroxylation of the corresponding olefin, while the 15-iodo-olefin corresponding to the C11–C15 part was prepared via the asymmetric transfer hydrogenation of the corresponding acetylene ketone followed by hydrozirconation/iodination. Both pieces were joined by a Sonogashira coupling, and the product was further converted into the title compound via a Wittig reaction with the remaining C1–C10 segment and Boland reduction using Zn with TMSCl.
Keywords: DHA metabolite; trihydroxylated DHA; organic synthesis; enyne; Boland reduction; TMSCl; Hansen protocol